Exploring the Transformative Potential of Maggot Meal (Hermetia illucens) in Tilapia (Oreochromis niloticus) Aquaculture - Mustafa Arifuzzaman; Agus Pangestu (IHSA Institute, 2023)
This research delves into the potential impact of incorporating maggot meal derived from Hermetia illucens into commercial tilapia (Oreochromis niloticus) feed. The study explores the multifaceted implications of this alternative protein source, spanning sustainability, growth performance, nutritional quality, and economic viability in the context of aquaculture practices. Our findings reveal a transformative potential for maggot meal, as it aligns with principles of sustainability by repurposing organic waste, accelerates tilapia growth rates, enhances feed conversion ratios, and enriches the nutritional composition of tilapia flesh. The practical implications and versatility of maggot meal in feed formulations, waste management, and potential applications across aquaculture species are also discussed. Moreover, the economic feasibility and market potential for maggot meal-derived tilapia products underscore its role as a key player in shaping the future of sustainable and economically viable aquaculture practices. This research serves as a foundation for further exploration, advocating for the adoption of innovative solutions that contribute to the resilience and responsibility of the aquaculture industry.